Pengaruh Ukuran Butiran Kapur Pertanian yang Diberikan Berdasarkan Sulfat Larut terhadap Peningkatan pH Tanah Sulfat Masam - Ramzy Nurul Afiat; Muhammad Mahbub; Zuraida Titin Mariana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Acid sulfate soils contain pyrite and when pyrite is oxidized it causes the soil pH to decrease. Application of agricultural lime CaCO3 is needed to raise soil pH. The grain size of lime greatly affects the fast, slow, and persistent increase in soil pH. This research method used a completely randomized design (CRD) with a single factor, namely the grain size of agricultural lime (18-35 mesh, 18-70 mesh, <18 mesh, 35-70 mesh, <35 mesh, <70 mesh). The treatment was repeated 4 times. The dose of lime given is based on the value of the bulk density of the soil and the sulfur of the soil solution. Observation of soil pH was carried out after an incubation period of 4 weeks using glass electrodes with various ratios of soil and water (1:2.5; 1:5; 1:7.5; 1:10). The results showed that the grain size of lime affects the increase in pH of acid sulfate soil in the soil-water ratio measurement method of 1:5 and 1:10, except for the measurement method 1:2.5 and 1:7.5. The smaller the lime size, the greater the increase in pH of acid sulfate soil. The largest increase in soil pH in the soil-water ratio measurement method was 1:10, for each grain size from the largest to the smallest: 18 - 35 mesh, 18 - 70 mesh, <18 mesh, 35 - 70 mesh, <35 mesh and <70 mesh, resulting in soil pH successively: pH 4.52; pH 4.58; pH 4.53; pH 4.60 ; pH 4.63 and pH 4.70.